Rethinking Intuition in Constructive Mathematics. - Bentzen, Bruno (Theoria: A Swedish Journal of Philosophy, 2025)
I propose an account of intuition for Bishop's brand of constructive mathematics, where constructions are person programs determined by their computational meaning. Past attempts to elucidate intuition by Parsons and Tieszen drawing on views put forward by Hilbert and Husserl, respectively, have failed to accommodate Bishop's ideas. I argue that, starting from premises building on the works of Brouwer and Heyting on the intuition of units and pairs and their causal sequences, we can explain how we intuit constructions by how their computational meaning is captured by causal relations we project on units and pairs. My exposition of these premises builds on Heyting's reinterpretation of Brouwer's thought and further develops a diagrammatic interpretation proposed recently with the introduction of computations through protentions.